Structure and Stability of Copper-Chelating Peptides Produced by Aspergillus oryzae in Solid-State Fermentation on Soybean Meal - WEN Zixuan, ZHOU Yue, HUANG Zhenghua, LI Bin, LIU Yuhuan, ZHENG Fengman, CAO Leipeng, (Shipin Kexue)
This study aimed to prepare copper-chelating peptides from soybean meal (SBMP-Cu(II)) using Aspergillus oryzae in solid-state fermentation and to investigate the chelation mechanism, structure and stability of SBMP-Cu(II). The results showed that peptides from soybean meal peptides (SBMP) with molecular masses of 1–5 kDa had a strong chelating capacity toward Cu2+, and the Cu2+ chelating capacity reached up to (288.47 ± 2.18) mg/g after purification by weak anion-exchange chromatography and gel filtration chromatography. A total of 27 oligopeptides with molecular masses of less than 1 500 Da were identified from the 1–5 kDa SBMP by liquid chromatography-tandem mass spectrometry (LC-MS/MS), and acidic (aspartic acid and glutamic acid) and basic amino acids (arginine, histidine and lysine) played a key role in the chelation of Cu2+. Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and zeta potential analysis showed that the major active groups in SBMP involved in its chelation with Cu2+ were –COOH and –NH2, and SBMP-Cu(II) had a higher crystallinity, with the formation of roughly spherical agglomerates caused by the neutralization of charges on the surface. In addition, SBMP-Cu(II) showed stronger resistance to acid, heat and salt as well as higher in vitro digestive stability than SBMP, suggesting that SBMP-Cu(II) has the potential to improve Cu2+ bioavailability as a new copper supplement. These results provide a theoretical basis and technical support for the low-cost and efficient preparation of SBMP-Cu(II) supplements and the high-value resource utilization of soybean meal.